PENGARUH PROFITABILITAS, HARGA SAHAM DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Kurniawan, Andrie; Winardi, Muhammad Aziz; Suntoro, Bambang; Hernawan, Iman (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to analyze the effect of profitability, stock price, and company size on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange. The research method used is descriptive and multiple linear regression. The data used are annual financial statements that have been audited from 2017 to 2021. The results show that there is no significant effect between profitability and company size on dividend policy. There is a significant influence between stock prices and dividend policy. Firm size has no significant effect on dividend policy. A company's dividend policy is affected by a complex set of factors, including profitability, share price, and company size. Company management needs to consider stock prices as an important factor in making dividend policy decisionsKey words: Profitability, Share Price, Company Size, Dividend